(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2015)
The phenomenon of using lures among Malay traders is very widely seen. The types of lure focused on in this article are lures that have some mystical features involving the supernatural, and those of local knowledge known only to a few practitioners. For example, the use of amulets, talismans, ibu duit (lit."money mother", i.e. money multipliers), wafaq (mystical diagrams) and images of pious people which are popular lures. This article aims to examine the phenomenon of lures by using the Islamic faith as a tool to analyse whether the use of such conflict with Islamic teachings. A literature review was conducted to obtain data on the perspective of the Islamic faith towards lures, while a field study involving interviews and observations of informants and business premises in the northern region of Peninsular Malaysia. The study found that there are some Malay traders who still use the lures such as wafaq, amulets, and images of pious people. They believe that such lures will bring in good business. The study also found that believing in the power of lures without bearing in mind that Allah is the Provider may lead to the sin of shirk (believing in a power other than Allah). Keywords: lure, Malay traders, aqidah, wafaq, amulets